The Dynamics of Triangulation in Cervantes’s El amante liberal - Collins, Marsha S. (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2021)
This essay analyzes Miguel de Cervantes’s El amante liberal as a type of psychomachia that dramatizes the battle between two systems of interpersonal triangulation that change and mold the conduct and character of the protagonist Ricardo, and to a degree, of the other protagonist Leonisa. René Girard’s mimetic desire, which degrades and dehumanizes individuals, and St. Thomas Aquinas’s Christian friendship, which foments love and generosity, are inscribed in the story to explore the theme of identity and offer a Cervantine paradigm of reading and interpretation. This paradigm allows for ambiguity, hybridity, and changing interpretations.